Współczynnik intelektualnej wartości dodanej (VAIC™) w ocenie efektywności gospodarowania zasobami przedsiębiorstwa na przykładzie wybranych spółek giełdowych - Szczepankowski, Piotr (The Value Added Intellectual Coefficient (VAIC™) as the Measure of a Firm's Resources Efficiency on the Example of Publicly Traded Companies, 2006)
The purpose of this paper is to investigate the association between efficiency of value added of the major components of a firm's resources and three traditional dimensions of corporate performance (assets profitability, productivity, market valuation). Data from 2003 annual reports are drawn from an example of eight publicly traded companies from two business sectors heavily reliant on intellectual capital (telecommunication and media and publishing firms). The empirical findings suggest both physical and intellectual capital (measured by the VAIC™) remain the most significant underlying resources of corporate performance in Poland and show high positive correlation between company's market value and its the Value Added Intellectual Coefficient (VAIC™). Therefore, in Poland intellectual capital continues to overtake physical capital as the key asset of the corporation efficiency.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 599-617